Analisis Pembelajaran Diferensiasi Pada Kelas Yang Memiliki Peserta Didik Dengan Berkebutuhan Khusus - S, Chelsi Yuliana; Rusli, Tiffany Shahnaz (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2025)
This study aims to identify the implementation of differentiated instruction in classes with students with special needs, evaluate its effectiveness, and provide recommendations for improvement. The research employed a descriptive qualitative method at SD Inpres SKP F3 Arso, collecting data through interviews, observations, and documentation. The findings revealed  that the implementation of differentiated instruction, through content, process, and product classification, successfully enhanced the academic achievement and socio-emotional development of students with special needs. Teachers demonstrated  a good understanding of adapting teaching strategies to meet individual students needs. Challenges such as limited teachers knowledge of differentiated instruction can be addressed through training and collaboration with experts. This study concludes that differentiated instruction is an effective solution for improving the quality of learning in inclusive classrooms. Recommendations include teacher training development and registering the school as an inclusive institution.